If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + -1g = am + 5 Reorder the terms: -1g + 3m = am + 5 Reorder the terms: -1g + 3m = 5 + am Solving -1g + 3m = 5 + am Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-3m' to each side of the equation. -1g + 3m + -3m = 5 + am + -3m Combine like terms: 3m + -3m = 0 -1g + 0 = 5 + am + -3m -1g = 5 + am + -3m Divide each side by '-1'. g = -5 + -1am + 3m Simplifying g = -5 + -1am + 3m
| 2x-15=29 | | d=60t | | lnX=9.9 | | 35x^3-x^3= | | -y-4x=-17 | | x-0.3x=646.14 | | 4x^2-23x+19=-6x+4 | | 2y-4x=-26 | | x-1500=1534.75-866.25 | | 6q+12=0 | | x+7y+42=0 | | C(Q)=1500-12.5Q+0.01Q | | 7x-92= | | (8+w)(4w+1)=0 | | -5=-2x-3 | | x*.13+x=253.39 | | 5x+3y+2x+4y= | | 1500+x-1534.75=866.25 | | 7x+15=2(x-5) | | 3(x+8)=2[x-(8-x)] | | 18x-22+50=180 | | x*.13+x=1775.87 | | -3x+10y+10=0 | | X+y=124 | | f=3x+6y | | x*.13=1775.87 | | 6y-y+5y-6y= | | 9+2x=56 | | 4x-12=50 | | 0.824x+x=0.450 | | 5/8p=8 | | x+x=500 |